Evaluation of Diving Sports Development in South Kalimantan - Lazuardy Akbar Fauzan; Edwin Wahyu Dirgantoro; Listiyani (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
Diving is a water sport that has developed into an achievement sport. The development of diving in South Kalimantan began to develop from the level of educational institutions to government institutions. The condition of the South Kalimantan region which has most of the water area, both in the form of rivers, swamps, beaches, and lakes, makes diving quite attractive and developed into a sport of achievement and the field of SAR. This study aims to evaluate the development of diving sports achievement in South Kalimantan. The research method used in this research is descriptive qualitative. The evaluation approach used with the CIPP model includes a discussion of the Context, Input, Process, and Product of the ongoing diving coaching process. Data collection techniques by conducting interviews, observations and documentation studies. The data obtained were analyzed qualitatively with the following steps: 1) data reduction, 2) data presentation, and 3) drawing conclusions. The results showed that 1) the evaluation of the context was in accordance with the coaching program, 2) the evaluation of the inputs was not in accordance with the coaching program. 3) process evaluation is not in accordance with the established criteria 4) product evaluation is appropriate but performance still needs to be improved.